The Strategies in Learning English Listening Skills Used by The Eighth-Graders - Mery Eka Wahyuni; Nina Inayati (Journal of Foreign Language Teaching and Learning, 2022)
Listening is a receptive skill that plays a crucial role in learning English because it is a language modality used in direct conversation. This study determined the strategies used by the eighth-graders in English listening lessons and their reasoning. This study implemented a mixed-method approach and was carried out in a private junior high school in Probolinggo, involving 62 students. To collect the data, the researchers employed surveys and interviews to determine the types of student learning strategies in listening lessons and the reasons for using these strategies. The survey data were analyzed quantitatively using weighted means, while the qualitative data from the interview were thematically analyzed. The findings indicated that the most used strategies were metacognitive (x=3.77), cognitive (x=3.69), and social-affective (x=3.40). Next, students’ reasons for using the metacognitive strategies would understand the topic, think about the learning process, and evaluate evaluations that help them do the listening test. Students could understand the meaning of the topics they hear, make students focus on learning objectives, and know the progress of learning applied. By knowing students' learning strategies and their reasons, teachers can be more creative in choosing the proper learning methods because they know students' character and what they need.